Chemical composition, in-vitro fermentation and methane production potential of unconventional feed resources in goats - TRIPATHI, M K; MEENA, RAMKESH; RAHAL, ANU; TRIPATHI, PRABHAT; KUMAR, RAVINDRA; CHAUDHARY, U B; GUPTA, D L (The Indian Journal of Animal Sciences, 2016)
Unconventional feed resources namely Aloe barbadensis (ALB), Musa paradisiaca (MUP), Punica granatum (PUG), Murraya koenigii (MUK), Lawsonia inermis (LOI) and Boehravia diffusa (BOD) were assessed for in- vitro methane production potential and fermentation with whole goat rumen flora. Nutrient content of all the bio- resources were different, and the gas production varied from 57.7 to 161.7 ml/ g DM, with the highest gas in ALB and the lowest in BOD. Although, gas production was different among all feed resources, however gas production for each gram DM fermented was similar in MUP, PUG, MUK and LOI leaves. Methane production ranged from 6.7 to 18.9 g and 10.5 to 22.83 g/ kg DM and g/ kg fermented DM respectively. The energy loss in the form of methane also followed the trend of gas production, which ranged from 11.4 to 17.1% of digestible energy. Therefore, feed resources with varying nutrient contents have significant variations in fermentability and methane production potential.